(untitled) (Journal of Mathematical Study, 2023)
The study of asymptotically hyperbolic Einstein metric is a rich field in theoretical physics and geometry. Pedersen introduced a family of examples for the dimension 4, and we look in this paper into the sign of some of its conformal invariant, namely renormalized volume and Yamabe-type constant. This brings some insights in the study of conformally compact Einstein manifold, as the comparison of invariants is already common practice.